Sociocultural Determinants of Policewomen–Taxi Drivers’ Interactions on the Major Highways in Ibadan Metropolis, Nigeria - Ojedokun, Usman Adekunle (Women & criminal justice, 2019)
This study investigated the sociocultural determinants of policewomen-taxi drivers’ interactions on the major highways in Ibadan metropolis. Purposive sampling technique was utilized for the selection of 11 policewomen and 35 taxi drivers. Data were generated through key informant interview and focus group discussion methods. Findings revealed that gender had no impact on the ability of policewomen to enforce traffic law. Policewomen were adjudged to be strict on traffic law enforcement. However, the size of the accolade generated by this feat has been slightly attenuated by the action of officers who habitually demand for bribe from apprehended taxi drivers.